Oxidative balance score is associated with the risk of diabetic kidney disease in patients with type 2 diabetes mellitus: evidence from NHANES 2007–2018 - Liang, Yu; Xu, Zhonggao; Wang, Wanning (Frontiers in Nutrition, 2024)
ObjectiveThe oxidative balance score (OBS) is a comprehensive measure of oxidative stress that is calculated from the combined prooxidant and antioxidant scores of 16 dietary components and four lifestyle factors. This study aimed to evaluate the relationship between OBS and the risk of diabetic kidney disease (DKD) in individuals with Type 2 diabetes mellitus (T2DM).MethodsData were obtained from the NHANES. A cross-sectional study was conducted using multiple logistic regression. Covariate effects of this relationship were also examined using subgroup analysis.ResultsWe evaluated 3,669 T2DM participants, among whom DKD prevalence was 30.87%. In a fully adjusted logistic regression model, the risk of DKD among participants with OBS, lifestyle OBS, and dietary OBS in the highest quartile group was 0.50 times (95% CI: 0.39 to 0.65), 0.54 times (95% CI: 0.41–0.71), and 0.45 times (95% CI: 0.32–0.63), respectively, than that in the lowest quartile group, respectively. In addition, participants who scored in the top quartiles of OBS were more likely to possess higher levels of education and income. A stratified analysis demonstrated the robustness of these findings.ConclusionOBS negatively correlates with the risk of DKD among individuals with T2DM.